DIGITAL NATIVE ASSESSMENT SCALE: REVISITING THE CONCEPT OF DIGITAL NATIVENESS FROM TEACHERS’ RESPONSES - Agustin, Fitri; Lengkanawati, Nenden Sri; Muslim, Ahmad Bukhori (International Journal of Education, 2024)
The phrase "digital native," which is used almost universally to describe the use of technology by today's teachers and students, is laden with debate both regarding its meaning and how it should be measured. The Digital Natives Assessment Scale (DNAS) was established, developed, and validated to assess "digital nativeness." This study contributes to the ongoing dispute regarding the validity of the DNAS, which Wilson (2020) had previously reported in the literature. Seventy-eight Indonesian secondary school teachers joined the survey and two of the respondents were invited to join the semi-structured interview. The findings of the study provided the data for the examination of how the DNAS addresses the factors that contribute to digital nativeness. The results from the DNAS corroborated Wilson's claim that the DNAS may not address the features of digital natives. This study recommends that future research in the realm of educational technology and beyond should concentrate on different ways of conceiving the concept of digital natives.